2013
DOI: 10.1186/1475-2875-12-254
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of artemether-lumefantrine and dihydroartemisinin-piperaquine in the treatment of uncomplicated malaria among children in western Kenya

Abstract: BackgroundArtemether-lumefantrine (AL) was adopted as first-line treatment for uncomplicated malaria in Kenya in 2006. Monitoring drug efficacy at regular intervals is essential to prevent unnecessary morbidity and mortality. The efficacy of AL and dihydroartemisinin-piperaquine (DP) were evaluated for the treatment of uncomplicated malaria in children aged six to 59 months in western Kenya.MethodsFrom October 2010 to August 2011, children with fever or history of fever with uncomplicated Plasmodium falciparum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 26 publications
(28 reference statements)
2
25
0
Order By: Relevance
“…Recent changes suggest that we should reconsider the use of aminoquinolines to treat malaria, including AS-AQ, which showed inferior efficacy to AL in Tanzania (54) and Uganda (55,56) some years ago but excellent recent efficacy in West and Central Africa (57-61); DP, which has shown excellent efficacy (7,(62)(63)(64)(65)(66); and perhaps combinations that include chloroquine (52,67). Further, we should be cautious regarding the long-term antimalarial efficacy of AL, as although both the clinical efficacy of AL (57)(58)(59)(60)(61)(64)(65)(66) and ex vivo activity of DHA and lumefantrine (31,42,(68)(69)(70) ies, current results suggest that the antimalarial potency of lumefantrine is decreasing. Our data show that antimalarial treatment regimens rapidly select for parasites with decreased drug sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent changes suggest that we should reconsider the use of aminoquinolines to treat malaria, including AS-AQ, which showed inferior efficacy to AL in Tanzania (54) and Uganda (55,56) some years ago but excellent recent efficacy in West and Central Africa (57-61); DP, which has shown excellent efficacy (7,(62)(63)(64)(65)(66); and perhaps combinations that include chloroquine (52,67). Further, we should be cautious regarding the long-term antimalarial efficacy of AL, as although both the clinical efficacy of AL (57)(58)(59)(60)(61)(64)(65)(66) and ex vivo activity of DHA and lumefantrine (31,42,(68)(69)(70) ies, current results suggest that the antimalarial potency of lumefantrine is decreasing. Our data show that antimalarial treatment regimens rapidly select for parasites with decreased drug sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The longer half-life results in a longer posttherapeutic prophylactic effect and a decreased reinfection rate in the first 28 days compared with AL (38). However, theoretically, the longer half-life could also potentially increase the risk of selection of resistance to piperaquine (39).…”
Section: Discussionmentioning
confidence: 99%
“…8 A variety of ACTs exists, such as artemether-lumefantrine (AL) and dihydroartemisinin-piperaquine (DP), which vary in their efficacy profile against uncomplicated malaria, tolerability, and their ability to reduce infectivity to mosquitoes. 8,[11][12][13][14] The difference in efficacy between these ACTs may have important implications not only for the treatment of individual patients, but also for the population-level impact on malaria transmission. 11,13 The balance among these factors, which may themselves vary between communities, will determine whether AL or DP is optimal in different settings.…”
Section: Introductionmentioning
confidence: 99%
“…8,15,16 Comparative efficacy studies in multiple settings have consistently reported a longer duration to recurrent infection in individuals treated with DP as compared with AL. 13,14 At the population level, DP has drawbacks in terms of its relative effectiveness in reducing malaria transmission, compared with AL. A recent clinical trial conducted among Kenyan children has shown that despite the longer post-treatment prophylactic period of DP compared with AL, individuals treated with DP may have a longer infectious period and resultant higher malaria transmission potential to mosquitoes after treatment than those treated with AL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation